Reduced global positioning system (GPS) positioning error by mitigating ionospheric scintillation - Ho, Yih Hwa; Abdullah, Sabirin (2014)
GPS has diverse application in current globalized world, its application has pervasive benefits not only to navigation and positioning, it is pivotal in industries like logistics, shipping, financial services and agriculture. Since the decision to shut down the Selectivity Availability (SA) by former U.S. President, Bill Clinton, ionospheric effect is now the primary concern of error contributing factors in GPS. Ionospheric scintillation induces rapid fluctuations in the phase and the amplitude of received GNSS signals. These rapid fluctuations or scintillation potentially introduce cycle slips, degrade range measurements, and if severe enough lead to loss of lock in phase and code. Global Ionospheric Scintillation Model (GISM) was used to compute amplitude scintillation parameter for each GPS satellite visible from Melaka, Malaysia (Latitude 20 14' N, Longitude 1020 16' E) as its location has strong equatorial scintillation behavior. The output data from GISM was then used to calculate the positioning error where it is depends on the Dilution of Precision (DOP) and User Equivalent Range Error (UERE). There are five schemes that were used. First, the positioning error was calculated for all the visible satellites with mask angle > 50. Secondly, the positioning error was calculated for 6 satellites that having lowest UERE. Thirdly, the positioning error was calculated for all the visible satellites with mask angle > 100. Fourthly, the positioning error was calculated for those satellites that have amplitude scintillation index, S4 <; 0.7. Lastly, the positioning error was calculated for those satellite having outliers> 10% of mean S4 for all satellites. Comparison of results from these schemes were then made.